RISK FACTORS THE INCIDENCE OF MALARIA IN THE DISTRICT OF KEMIRI PURWOREJO REGENCY - Lilik Setyowatiningsih; Surati Surati (Poltekkes Kemenkes Semarang, 2020)
Malaria is caused by protozoa of the genus plasmodium which infect red blood cells. Malaria cases in Kemiri Subdistrict, Purworejo Regency in 2006 were 13 cases and in 2016 malaria reappeared with 44 cases. The purpose of this study was to determine the risk factors associated with the incidence of malaria in Kemiri District, Purworejo Regency. The benefits of this research are adding information to the public about risk factors associated with malaria in the Kemiri District, Purworejo Regency. This type of research is observational research with analytic criteria. The variables of this study are malaria incidence and risk factors which include education, knowledge, employment, use of mosquito nets and environmental sanitation. The population and sample in this study were citizens in the Kemiri District, Purworejo Regency. Based on the results of laboratory tests all respondents (87 people) 100% tested negative for malaria. Bivariate test results showed that there was no significant relationship between the incidence of malaria with education (p=0.845), knowledge (p=0.359), community behavior (p=0.524) and environmental sanitation (p=0.095).